Cathelicidins from the Bullfrog Rana catesbeiana Provides Novel Template for Peptide Antibiotic Design - Guiying Ling; Jiuxiang Gao; Shumin Zhang; Zeping Xie; Lin Wei; Haining Yu; Yipeng Wang (2014)
Cathelicidins, a class of gene-encoded effector molecules of vertebrate innate immunity, provide a first line of defense against microbial invasions. Although cathelicidins from mammals, birds, reptiles and fishes have been extensively studied, little is known about cathelicidins from amphibians. Here we report the identification and characterization of two cathelicidins (cathelicidin-RC1 and cathelicidin-RC2) from the bullfrog Rana catesbeiana. The cDNA sequences (677 and 700 bp, respectively) encoding the two peptides were successfully cloned from the constructed lung cDNA library of R. catesbeiana. And the deduced mature peptides are composed of 28 and 33 residues, respectively. Structural analysis indicated that cathelicidin-RC1 mainly assumes an amphipathic alpha-helical conformation, while cathelicidin-RC2 could not form stable amphipathic structure. Antimicrobial and bacterial killing kinetic analysis indicated that the synthetic cathelicidin-RC1 possesses potent, broad-spectrum and rapid antimicrobial potency, while cathelicidin-RC2 exhibited very weak antimicrobial activity. Besides, the antimicrobial activity of cathelicidin-RC1 is salt-independent and highly stable. Scanning electron microscopy (SEM) analysis indicated that cathelicidin-RC1 kills microorganisms through the disruption of microbial membrane. Moreover, cathelicidin-RC1 exhibited low cytotoxic activity against mammalian normal or tumor cell lines, and low hemolytic activity against human erythrocytes. The potent, broad-spectrum and rapid antimicrobial activity combined with the salt-independence, high stability, low cytotoxic and hemolytic activities make cathelicidin-RC1 an ideal template for the development of novel peptide antibiotics.